2015
DOI: 10.1002/hed.24189
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and perioperative complications in head and neck free tissue reconstruction

Abstract: Background Free tissue transfer is a mainstay in reconstruction of complex head and neck defects. The purpose of this study was to determine if perioperative complications were more common in patients with body mass index (BMI) >30 kg/m2 undergoing free flap reconstruction. Methods A multi-institutional retrospective cohort was created. Medical complications, surgical complications, and procedural variables were recorded. Logistic regression was used to investigate univariate and multivariate associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 13 publications
3
33
0
Order By: Relevance
“…Therefore, these results are in agreement with existing reports specific to head and neck free flaps in finding no significant increase in operative morbidity in obese patients. 8,9 However, this analysis increases the validity of this conclusion, as comparisons were made to normal-weight controls rather than to all patients with nonobese BMI.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, these results are in agreement with existing reports specific to head and neck free flaps in finding no significant increase in operative morbidity in obese patients. 8,9 However, this analysis increases the validity of this conclusion, as comparisons were made to normal-weight controls rather than to all patients with nonobese BMI.…”
Section: Discussionmentioning
confidence: 92%
“…In a study aiming to analyse how BMI affects infectious complications in free tissue transfer surgery 20 , the authors failed to note a positive association, and a similar finding was also reported by de la Garza et al . 21 . However, both Lo et al .…”
Section: Discussionmentioning
confidence: 99%
“…A higher percentage of diabetic patients were found to have obesity, which is expected given the well‐known association between obesity and the development of insulin resistance (Kahn, Hull, & Utzschneider, ; Nguyen, Nguyen, Lane, & Wang, ). Interestingly, prior studies have shown that obesity may be associated with a decreased risk of head and neck cancer, and increased BMI is not a predictor of postoperative medical or surgical complications in patients undergoing head and neck free flap surgery (de la Garza et al, ; Tan et al, ).…”
Section: Discussionmentioning
confidence: 99%